A comparison of different banking system’s performance during global financial crisis: Islamic vs conventional / Ruslin Mohamed Redwan - Mohamed Redwan, Ruslin (2013)
The main purpose of this paper is to measure and analyze the performance of conventional and Islamic banking system during the financial global crisis in Malaysia. A total of 4 local banks that provide two different banking systems are selected as a sample. The performance of both banks is measured in terms of liquidity, leverage and efficiency. The study covers 7 years period from 2006 to 2011 and divide the period into pre, during and post global financial crisis. The comparison is made between the performances of conventional banking with the Islamic banking in Malaysia using financial ratios, graph models and Independent T-Test. To test the hypothesis correlation coefficients of Pearson and multiple regression models are used in determining their significance. The result showed that in terms of leverage, return on equity and efficiency, conventional is performing better than Islamic and for the liquidity risks, Islamic banking system performed well than conventional banking system